Galerie Michael Haas, Galerie Haas & Fuchs Berlin 2006. - Publikation anlässlig 'Art 37 Basel' im Art in Basel, 14.06.2006-18.06.2006; Art, Basel (Basel : Art Basel, 2006)
Auerbach, Frank ; Dokoupil, Jiri Georg ; Estes, Richard ; Fontana, Lucio ; Gartner, Marianna ; Gertsch, Franz ; Hodgkin, Howard ; Jahns, Rudolf ; Kiefer, Anselm ; Kirchner, Ernst Ludwig ; Kirkeby, Per ; Kluge, Gustav ; Lausen, Uwe ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Meese, Jonathan ; Mondriaan, Piet ; Ottersbach, Heribert C. ; Pearlstein, Philip ; Polke, Sigmar ; Rainer, Arnulf ; Rouault, Georges ; Schwitters, Kurt ; Soutter, Louis ; Vantongerloo, Georges ; Vasarely, Victor
boek